Estudio sobre el autoconcepto de los alumnos del 1ero. de secundaria de una I.E. del distrito de Ventanilla - Medina Coronado, Daniela (2010)
The aim of this research was to describe the self concept of first year high school students in a Ventanilla’s school. 150 subjects were taken for the sample, 75 male students and 75 female students. Their ages were between 11 to 15 years old. The results obtained by the Self-Concept Questionnaire in the school of Andrés García, show that most students surveyed have a high average and general self-concept, it appears that socio-economic factor that comes from the sample has not affected their self-concept of. We also found that males have a better emotional self-concept than females. While women had higher levels on the social dimension. There was no difference in the physical dimension with respect to gender.